Fracture Behavior of a 2D Imine‐Based Polymer - Bowen Zhang; Xiaohui Liu; David Bodesheim; Wei Li; André Clausner; Jinxin Liu; Birgit Jost; Arezoo Dianat; Renhao Dong; Xinliang Feng; Gianaurelio Cuniberti; Zhongquan Liao; et al. (Advanced Science)
Abstract 2D polymers have emerged as a highly promising category of nanomaterials, owing to their exceptional properties. However, the understanding of their fracture behavior and failure mechanisms remains still limited, posing challenges to their durability in practical applications. This work presents an in‐depth study of the fracture kinetics of a 2D polyimine film, utilizing in situ tensile testing within a transmission electron microscope (TEM). Employing meticulously optimized transferring and patterning techniques, an elastic strain of ≈6.5% is achieved, corresponding to an elastic modulus of (8.6 ± 2.5) GPa of polycrystalline 2D polyimine thin films. In step‐by‐step fractures, multiple cracking events uncover the initiation and development of side crack near the main crack tip which toughens the 2D film. Simultaneously captured strain evolution through digital image correlation (DIC) analysis and observation on the crack edge confirm the occurrence of transgranular fracture patterns apart from intergranular fracture. A preferred cleavage orientation in transgranular fracture is attributed to the difference in directional flexibility along distinct orientations, which is substantiated by density functional‐based tight binding (DFTB) calculations. These findings construct a comprehensive understanding of intrinsic mechanical properties and fracture behavior of an imine‐linked polymer and provide insights and implications for the rational design of 2D polymers.